2017
DOI: 10.2147/jpr.s128655
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and consensus recommendations for the pharmacological management of pain in India

Abstract: Despite enormous progress in the field of pain management over the recent years, pain continues to be a highly prevalent medical condition worldwide. In the developing countries, pain is often an undertreated and neglected aspect of treatment. Awareness issues and several misconceptions associated with the use of analgesics, fear of adverse events – particularly with opioids and surgical methods of analgesia – are major factors contributing to suboptimal treatment of pain. Untreated pain, as a consequence, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 251 publications
(283 reference statements)
0
28
0
1
Order By: Relevance
“…[353637] Indian medical practitioners have vocalized the need to have culturally appropriate guidelines that are created keeping in mind, the regulatory policies and lack of prior training opportunities. [10383940] The assessment of knowledge showed that most participants (71%) accurately expressed that opioid analgesics should be the mainstay of moderate-to-severe cancer pain treatment, and this response was significantly associated with having prior knowledge of the WHO ladder. Studies in the Southeast Asian region and assessments of prescription patterns for Indian cancer patients too have shown that most of them received opioid analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…[353637] Indian medical practitioners have vocalized the need to have culturally appropriate guidelines that are created keeping in mind, the regulatory policies and lack of prior training opportunities. [10383940] The assessment of knowledge showed that most participants (71%) accurately expressed that opioid analgesics should be the mainstay of moderate-to-severe cancer pain treatment, and this response was significantly associated with having prior knowledge of the WHO ladder. Studies in the Southeast Asian region and assessments of prescription patterns for Indian cancer patients too have shown that most of them received opioid analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…The current armamentarium for pain management comprises multiple options, the majority based on monomodal mechanisms of analgesia [19,20]. However, acute pain is multidimensional in nature, involving sensory, affective, cognitive, and behavioural aspects.…”
Section: Current Challenges In and The Available Options For The Efmentioning
confidence: 99%
“…However, acute pain is multidimensional in nature, involving sensory, affective, cognitive, and behavioural aspects. Therefore, achieving adequate pain control with a single drug may not be beneficial [19,20]. Moreover, most analgesics exhibit a ceiling of efficacy and have significant safety concerns [21].…”
Section: Current Challenges In and The Available Options For The Efmentioning
confidence: 99%
“…11,[14][15] Various adjuvant analgesics antiepileptics (Phenytoin, oxcarbamazepine, lamotrigine, topiramate, gabapentin, pregablin), antiarrythmics (Lignocaine and mexiletine) and clonidine, an alpha-2-agonist are commonly used for postherpetic neuralgia, trigeminal neuralgia and diabetic neuropathy. 16 Baclofen and tizanidine, the antispasmodic agents are routinely used against chronic pain. 10,16 A number of drug classes are often utilized for tackling chronic pain, but all the groups tend to produce some adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…16 Baclofen and tizanidine, the antispasmodic agents are routinely used against chronic pain. 10,16 A number of drug classes are often utilized for tackling chronic pain, but all the groups tend to produce some adverse effects. Hence, there is a need to look into new group of drugs.…”
Section: Introductionmentioning
confidence: 99%